Mechanical evolution of constant resistance and large deformation anchor cables and their application in landslide monitoring - Tao, Zhigang; Wang, Yong; Zhu, Chun; Xu, Huixia; Li, Gan; He, Manchao (Bulletin of engineering geology and the environment, 2019)
Landslides are a common disaster in open-pit mining and are difficult to effectively monitor and provide early warnings for with conventional methods. A remote monitoring and forecasting system for landslides is developed using constant resistance and large deformation (CRLD) anchor cable to control impact resistance, large deformation, and energy absorption. Slow tension and instantaneous impact are generated on the CRLD anchor cable during development and penetration of the sliding surface. Both the static tensile test and dynamic impact test verify that the CRLD anchor cables maintain a high constant resistance, large deformation, and high energy absorption under the action of impact force and static force. Under static tension and dynamic impact, the CRLD anchor cable has advantages of large deformation, high constant resistance, stable performance, and advanced critical landslide warning. By applying CRLD anchor cables to the monitoring of Nanfen open-pit slopes in China, the 2016-11-01 landslide was successfully forecasted 4 h prior to the event, guaranteeing mine safety and providing the theoretical and practical basis for an advanced monitoring and early warning for landslides.